PENGELOLAAN TAMAN MARGASATWA DAN BUDAYA KINANTAN KOTA BUKITTINGGI DALAM UPAYA MENUJU BADAN LAYANAN UMUM DAERAH - Sari, Dwi Astuti Purnama; Yuliani, Febri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Management of the zoo is very important, considering zoo is an asset that must be preserved. The zoo should be managed independently, so it can be arrenged well. Bukittinggi has the oldest zoo in Indonesia, it is Taman Margasatwa and Budaya Kinantan (TMSBK). Currently, TMSBK is managed by Development Culture and Tourism in Bukittinggi and has a status a Conservation Agency. According to TMSBK leader’s target, TMSBK should have been Badan Layanan Umum Daerah, considering it has been eight years into a Conservation Agency. According to directly observation, the problem is the management of TMSBK is not optimal. The purpose of this research is to knowing how the management of Taman Margasatwa and Budaya Kinantan and to knowing obstacle factor in the management of Taman Margasatwa and Budaya Kinantan in effort towards Badan Layanan Umum Daerah.The theory used is management by George R. Terry starting from planning, organizing, actuating and controlling. This research uses a qualitative descriptive method. In collecting the data researcher uses the method of observation, interview and documentation.The result of this research gets conclution that management by Departement Culture and Tourism in Bukittinggi is not optimal. There is still a shortage, especially in organizing and controlling by Departement Culture and Tourism in Bukittinggi. And then, obstacle factor in the management of Taman Margasatwa and Budaya Kinantan in effort towards Badan Layanan Umum Daerah, it is human resources, evaluation, permission from local leaders and visitors.Keywords: Management, Badan Layanan Umum Daerah